Optimal Virtual Machine Allocation and Migration Model Based on PCA-BFD - Garg, R (International Journal of Computer Sciences and Engineering, 2025)
This paper comprises of two sections, in the first section study the various energy aware best fit decreasing algorithms like BFD, MBFD, PCA-BFD, and EPOBF, and comparison has been done on the basis of past data. Study shows that PCA-BFD is the best algorithm for energy efficiency. In the second part of this paper PCA-BFD is used for migration purpose. First of all load of all host are evaluated and find the overloaded and under loaded server known as hot-spot node. That node whose load is balanced is considered as non hot-spot node. Virtual machines in hot-spot nodes are sorted in descending order so those high power consumption nodes migrate first. Non hot-spot nodes are sorted in ascending order so low power consumption server are firstly filled.